Unravelling the secrets of euro area inflation: A frequency decomposition approach - Dieter Gerdesmeier; Barbara Roffia; Hans-Eggert Reimers (Hochschule Wismar, Fakultät für Wirtschaftswissenschaften, 2018)
[Introduction] The role of money and credit for the economy, and especially for inflation, has always attracted a lot of attention in the economic literature (see, for instance, Friedman and Schwartz (1963), Bernanke (1993)) and, more recently, Nelson (2008), Benati (2009), Lucas and Nicolini (2015), Hevia and Nicolini (2017) as well as Anderson, Bordo and Duca (2017)). This paper addresses some key questions regarding the fundamental nature of the relationships among those variables and attempts to analyse them for the euro area by means of filter-design techniques. After decomposing the variables over different frequencies, regressions are carried out and the main drivers of inflation over different horizons are derived in a single-equation approach. Robustness checks are also carried out by choosing different combinations of explanatory variables, price measures (GDP deflator and house prices) and frequency horizons. The paper is structured as follows. After a review of the literature and methodology, the basic framework applied in the analysis as well as the relevant variables are illustrated in more details. Afterwards, the results at different frequencies for HICP, the GDP deflator and house prices are provided. The final section concludes.
Keywords: E31; E51; E52; 330